The Effect of the Internal Control System on the Effectiveness of Collection of Parking Retributions at the Majalengka Regency Transportation Service - Novelia Adzani Dirgajayanti; Fahrul Alam Masruri; Gunawan Wibisana (LPPM Universitas Sebelas April, 2020)
This study aims to determine: (1) To find out whether the internal control system in the Department of Transportation affects the collection of parking fees in Majalengka Regency, (2) To find out how effective the collection of parking fees by the Department of Transportation (Dishub) of Majalengka Regency is. The type of research used is a quantitative method with a survey approach. The results of this study indicate that (1) the Internal Control System has a significant and significant effect on the Effectiveness of Collection of Parking Retribution as indicated by the correlation coefficient value of 0.283, the significance value is less than the critical value, namely 0.050 or (0.013 <0.05) and the t-count value is 2.538. ttable is greater than 1,994, (2) the Internal Control System also has a correlation with the Effectiveness of Collection of Parking Retribution as indicated by the coefficient value of 0.283. Then the magnitude of the correlation between the Internal Control System and the Effectiveness of Collection of Parking Retribution when the Internal Control System remains is (0.283) x 100% = 28.3%